PENGARUH APRESIASI NON-FINANSIAL DAN DUKUNGAN ATASAN TERHADAP PRODUKTIVITAS KARYAWAN PADA PT PLN (PERSERO) UP3 MAKASSAR SELATAN - Nurfadilah Nurfadilah Nurfadilah (Universitas Teuku Umar, 2026)
This study aims to analyze the influence of non-financial appreciation and supervisor support on employee productivity at PT PLN (Persero) UP3 Makassar Selatan. Using a quantitative approach with a total sampling method of 50 respondents, data were processed using multiple linear regression via SPSS 26. Partial test results (t-test) show that non-financial appreciation (t = 5.251; sig = 0.003) and supervisor support (t = 4.516; sig = 0.000) have a positive and significant effect on productivity. Simultaneously (F-test), both variables significantly influence productivity with an F-value of 4.485. The coefficient of determination (R2) of 0.760 indicates that the independent variables contribute 76% to employee productivity, while the remaining 24% is influenced by other factors outside this study.Keywords: Non-Financial Appreciation, Supervisor Support, Employee Productivity.